A systematic review of climate adaptation planning in African cities - Madhi, Yasirah (Department of Environmental and Geographical Science, 2024)
In recent years the need for climate change adaptation has become increasingly important. Adaptation planning is understood to be the process by which actors identify, develop, test, and prioritise strategies and measures to reduce climate risk. In Africa, climate projections predict higher temperature increases than the rest of the globe. Africa is a rapidly urbanizing continent and its urban population is expected to rise to 59% by 2050. Thus, reducing climate risks and leveraging any emerging climate-related opportunities in cities will be a key component of tackling climate change across the continent. In the last few decades, the number of publications on climate adaptation has been increasing considerably. This growing body of climate adaptation research is in need of consolidation in order to draw meaningful lessons from place-specific and hazard-specific studies. This study aimed to collate and review peer-reviewed literature on climate adaptation planning in African cities in order to consolidate fragmented information and establish what is known about how climate adaptation is occurring at the urban scale. Using the systematic review process, relevant documents on the topic were identified and extracted using specific inclusion and exclusion criteria to delimit and broadly characterize the body of literature focusing on climate adaptation planning in an urban African context. Due to the scope and constraints of a minor dissertation, only a sub-set of documents underwent full-text review using thematic content analysis. The code used for thematic analysis was developed through an abductive process using Hunter et al. (2020) and Ford et al. (2015)'s coding categories as a framework. A total of 84 papers were considered suitable for inclusion. The geographical distribution of urban adaptation planning literature was established with most papers stemming from southern Africa (56), followed by East (19), West (17), and North Africa (5). No publications dealt with urban climate adaptation in Central Africa. The country with an overwhelming number of publications was South Africa (40). The majority of the literature was authored by researchers based in institutions outside of Africa (54%). Papers were broadly categorised into articles that tested, developed, prioritised, or identified strategies to reduce climate risk. The papers testing strategies to reduce climate risk were chosen for full-text analysis. South Africa was excluded from the final sub-set in order to focus on assimilating knowledge from elsewhere across the continent. 11 papers underwent the coding processes. Flooding was identified as the main climatic driver of adaptation and most papers emphasized the need for stakeholder engagement and communication. This study showed the value of applying a systematic review methodology to identify trends and consolidate research on the planning aspects of climate adaptation in African cities. It argues for extending the full-text thematic analysis to the entire set of literature identified to strengthen theory development based on empirical knowledge from urban African contexts.